Modification of Natural Carbolic Acid from Arpus wit Lemongrass Essential oil as a Disinfectant - wibiana wulan nandari; Faizah Hadi; Mitha Puspitasari; Susanti Rina Nugraheni; Titik Mahargiani (Eksergi, 2022)
Carbolic acid is a cleaning fluid or disinfectant that can be used to clean various kinds of surfaces, especially floors. Carbolic acid is used to prevent germs and viruses from growing so as to prevent disease and its spread. Most housewives often use chemical-based floor cleaners that are immediate or more practical. Long-term and too frequent use can be harmful to the body and the environment. Therefore, one solution to minimize this is to use natural ingredients that are already available and developed in Lubuklinggau City, such as lemongrass to be used as carbolic acid. The preparation begins by dissolving the arpus into the NaOH solution until it dissolves, then adding a mixture of pine oil, teepol and propylene glycol until everything is homogeneously mixed. Carbol is ready to use. The resulting product is carbolic floor disinfectant. Modified natural carbolic acid from arpus and lemongrass can be used as a disinfectant because based on the results of research that has been done it can kill E-coli bacteria and has a fairly high effectiveness with an inhibition zone of 19.2 mm.